The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1038/s41598-021-04139-1
|View full text |Cite
|
Sign up to set email alerts
|

Living in a pandemic: changes in mobility routines, social activity and adherence to COVID-19 protective measures

Abstract: Non-Pharmaceutical Interventions (NPIs), aimed at reducing the diffusion of the COVID-19 pandemic, have dramatically influenced our everyday behaviour. In this work, we study how individuals adapted their daily movements and person-to-person contact patterns over time in response to the NPIs. We leverage longitudinal GPS mobility data of hundreds of thousands of anonymous individuals to empirically show and quantify the dramatic disruption in people’s mobility habits and social behaviour. We find that local in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 55 publications
1
43
0
1
Order By: Relevance
“…This result provides supporting evidence to the effectiveness of these measures in limiting the number of close contacts among people and their potential in mitigating the spread of SARS-CoV-2. Coherent results were found in previous single-country 6 or multi-countries 5 , 7 , 48 data-driven studies as well as in previous modelling studies using fine-grained mobility data 49 , 50 . We also observed that a more limited impact of the mitigation interventions was found in Spain than in Italy, possibly due to the de-centralised approach to implementing these containment strategies in each of the 17 Autonomous Regions.…”
Section: Discussionmentioning
confidence: 47%
“…This result provides supporting evidence to the effectiveness of these measures in limiting the number of close contacts among people and their potential in mitigating the spread of SARS-CoV-2. Coherent results were found in previous single-country 6 or multi-countries 5 , 7 , 48 data-driven studies as well as in previous modelling studies using fine-grained mobility data 49 , 50 . We also observed that a more limited impact of the mitigation interventions was found in Spain than in Italy, possibly due to the de-centralised approach to implementing these containment strategies in each of the 17 Autonomous Regions.…”
Section: Discussionmentioning
confidence: 47%
“…Along with the home and work locations, the radius of gyration and the entropy are commonly used [18,19,23,25,27,53,58,59] indicators of human mobility, and were also determined for every subscriber.…”
Section: Mobility Metricsmentioning
confidence: 99%
“…Bushman et al [10], Gao et al [21], Hu et al [26] and Tokey [51] also analyzed effects of the stay-at-home distancing on the COVID-19 increase rate, in the US. Lucchini et al studied the mobility changes during the pandemic, in four US states [32].…”
Section: Arxiv:220211620v1 [Cssi] 23 Feb 2022mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing complexity of urban environments [1,2] and the crucial role played by human displacements in the diffusion of epidemics, not least the COVID-19 pandemic [3,4,5,6,7,8], have created a great deal of interest around the study of individual and collective human mobility [9,10,11]. The prevention of detrimental collective phenomena such as traffic congestion, air pollution, segregation, and epidemics spread, which is crucial to make our cities inclusive, safe, resilient, and sustainable [12,13,14], depends on how accurately we can predict and simulate people's movements within an urban environment.…”
Section: Introductionmentioning
confidence: 99%